(untitled) (Sebha University Conference Proceedings, 2024)
Libya, being rich in Limestone and basalt rocks, has substantial reserves estimated at several billion tonnes according to recent geological investigations. Therefore, studying the transport properties of these aggregates when used as coarse aggregates in concrete production is of paramount importance. This study examines the influence of local aggregate source and size on the water permeability resistance of 30 MPa plain strength concrete. Nine concrete mixes were prepared, incorporating three types of coarse aggregates: basalt, white limestone, and brown limestone, with sizes of 10 mm, 14 mm, and 20 mm. The concrete specimens were subjected to water penetration testing in accordance with the British standard (BS EN 12390-8:2019). The results reveal that, at a constant aggregate size, concrete samples containing basalt aggregate exhibited the lowest water penetration depth, followed by those with limestone aggregates. It was observed that the water penetration depth decreased significantly when smaller aggregate sizes were used. Correspondingly, the permeability coefficient also decreased as the aggregate size in the concrete mix was reduced. The concrete mixes with basalt aggregates demonstrated the lowest permeability coefficients across all the studied aggregate sizes, followed by the white limestone aggregates. This indicates that the basalt aggregates were more effective in limiting water penetration due to their lower porosity, less void content, and lack of chemical reactivity at the aggregate-paste interface.